3D diffraction imaging of fault and fracture zones via image spectral decomposition of partial images. (5th March 2019) - Protasov, M.I.; Gadylshin, K.G.; Tcheverda, V.A.; Pravduhin, A.P.
ABSTRACT: The paper presents 3D diffraction imaging based on the spectral decomposition of a different combination of selective or partial images. These images are obtained by the pre‐stack asymmetric migration procedure, which is weighted data summation. Spectral decomposition is done in the Fourier domain with respect to spatial dip and azimuth angles. Numerical examples with the application of different workflows for the synthetic and real data examples demonstrate detailed reliable reconstruction of the fractured zones and reliable reconstruction of fracture orientation on synthetic and real 3D data examples.